Similarity Search and Applications 5th International Conference, SISAP 2012, Toronto, ON, Canada, August 9-10, 2012, Proceedings - Navarro, Gonzalo; Pestov, Vladimir (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2012)
This book constitutes the proceedings of the 5th International Conference on Similarity Search and Applications, SISAP 2012, held in Toronto, Canada, in August 2012. The 14 full papers presented in this volume, together with 2 demo papers and 2 invited talks, were carefully reviewed and selected from 19 submissions. The papers deal with many of the most relevant aspects of similarity searching and are organized in topical sections named: new scenarios and approaches; improving metric data structures; facing scalability issues; searching in specific spaces; and new similarity spaces.